Tax Data Processing System: Case Study Shibgah Islam Nusantara Amanah Foundation - Alya Nur Riski; Muhammad Syukri; Oktavia Oktavia; Rini Risanti; Asep Suherman (LPPM STMIK Mardira Indonesia, 2023)
The expense information handling framework at the Shibgah Islam Nusantara Amanah Foundation is as yet done physically, according to the ongoing framework, information filing and duty information recovery have not been completed as expected and on time, where away it is constantly put away haphazardly, causing harm or harm. lost information, so looking for information for data requirements of benefactors consumes most of the day since they need to every year find and match documents. This framework is broke down and planned utilizing spellbinding investigation research strategies and OOAD (Object Oriented Analysis Design) framework improvement methods. The programming language utilized by this framework is PHP with XAMPP web server and PHPMyAdmin information base. This expense information handling data framework that has been made can assist establishment with staffing to find, and recap charge information that is given consequently and can decrease the degree of document harm and blunders in recording charge reports.